2006
DOI: 10.1007/s00259-005-0043-9
|View full text |Cite
|
Sign up to set email alerts
|

123/125I-labelled 2-iodo-L-phenylalanine and 2-iodo-D-phenylalanine: comparative uptake in various tumour types and biodistribution in mice

Abstract: [(123)I]-2-iodo-L: -phenylalanine and its D: -isomer are promising tumour diagnostic agents for dynamic planar imaging. They showed a high and similar uptake in all tested tumours. [(123)I]-2-iodo-D: -phenylalanine showed better tracer characteristics concerning radiation dose to other organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…[35] Some cancer cells such as C6 rat glioma, HeLa cervix carcinoma cells and R1M rhabdomyosarcoma have high expression of LAT1 but showed no upregulation of LAT2. [36, 37] In such cancer cells lack of expression of LAT2, FEP ([ 18 F] 2 ) might have advantage over FET ([ 18 F] 1 ). Further investigations are needed to identify the amino acid transport systems involved in the uptake process.…”
Section: Resultsmentioning
confidence: 99%
“…[35] Some cancer cells such as C6 rat glioma, HeLa cervix carcinoma cells and R1M rhabdomyosarcoma have high expression of LAT1 but showed no upregulation of LAT2. [36, 37] In such cancer cells lack of expression of LAT2, FEP ([ 18 F] 2 ) might have advantage over FET ([ 18 F] 1 ). Further investigations are needed to identify the amino acid transport systems involved in the uptake process.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in animal tumor models using the L-and [72,73]. Studies comparing radioiodinated 2-iodo-L-phenylalanine and 2-iodo-D-phenylalanine in tumorbearing animals demonstrated that the D-enantiomer uptake was lower than with the L-enantiomer in normal tissues but that the D-and L-enantiomer showed similar levels of tumor uptake [74]. Human studies with the D-and L-enantiomers of 2-iodo-phenylalanine also demonstrated lower uptake and faster clearance of the D-enantiomer [75].…”
Section: Amino Acid Transportmentioning
confidence: 98%
“…Decreasing these two metabolites may inhibit tumor growth [6]. Myo-inositol as a growth factor influenced the tumor growth rate.…”
Section: Page 13 Of 27mentioning
confidence: 99%